2008
DOI: 10.1021/es072044e
|View full text |Cite
|
Sign up to set email alerts
|

NDMA Formation during Chlorination and Chloramination of Aqueous Diuron Solutions

Abstract: Formation of the potent carcinogen N-nitrosodimethylamine (NDMA) during chlorine disinfection of water containing secondary amines is now generally acknowledged. The phenylurea herbicide diuron is one of the most widely used herbicides in California, has been frequently detected in California's water sources with a transient nature of appearance, and has a structure that suggests it might be an NDMA precursor. This study sought to quantify the potential for NDMA formation from aqueous diuron solutions under va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 18 publications
2
68
0
Order By: Relevance
“…Further, a recent study showed that NDMA may only account for~5% of the estimated total nitrosamines (Dai and Mitch, 2013). In general, these results suggested that disinfection by chlorine or chloramine and pre-oxidation during drinking water treatment could produce nitrosamines due to the presence of precursors, which is consistent with previous reports (Chen and Young, 2008;Kemper et al, 2010;W.J. Zhou et al, 2009;Q.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finisupporting
confidence: 87%
See 2 more Smart Citations
“…Further, a recent study showed that NDMA may only account for~5% of the estimated total nitrosamines (Dai and Mitch, 2013). In general, these results suggested that disinfection by chlorine or chloramine and pre-oxidation during drinking water treatment could produce nitrosamines due to the presence of precursors, which is consistent with previous reports (Chen and Young, 2008;Kemper et al, 2010;W.J. Zhou et al, 2009;Q.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finisupporting
confidence: 87%
“…Among the 11 river water sources, the concentrations of the three nitrosamines in 6 source waters (DWTPs 4,17,18,35,51, and 54) were above 50 ng/L, which was probably correlated to the contamination of source water as indicated by high DOC (6.83, 4.28, 3.95, 4.36, and 3.16 mg/L for DWTPs 4, 17, 18, 35, and 54, respectively), ammonia (0.79, 0.47, and 0.45 mg/L for DWTPs 17, 18, and 54, respectively), and nitrate (10.9, 3.26, 3.01, 5.95, and 2.98 mg/L for DWTPs 4, 17, 18, 35, and 54, respectively) levels. In previous studies, relationship between nitrosamine-FP and these water quality parameters has been observed (Chen and Young, 2008;Choi and Valentine, 2003). In addition, DWTPs 4, 17, 18, 35, 51, and 54 were located in the middle and downstream of the river sources, so contamination contributions from the industrial and domestic discharge of nitrosamines could not be neglected (Mitch et The ratio of the sum concentrations of the nine nitrosamines in finished water to those in source water was 42.3% on the 75th percentile value basis (Supplementary Table D); the median and maximum concentrations of the nine nitrosamines in this study were 9.95 ng/L and 153.2 ng/L, respectively, which is similar to the US and Canada survey results.…”
Section: Occurrence Of Multiple Nitrosamines In Source Water and Finimentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, selected agricultural chemicals have been found to be NDMA precursors. For example, the phenylurea herbicide diuron reacts with chlorine or chloramines, especially dichloramine, to form NDMA (Chen & Young 2008). Recently, the fungicide tolylfluanide was found to undergo microbial degradation to N,N -dimethylsulphamide, which during ozonation had a high conversion rate to NDMA (Schmidt & Brauch 2008).…”
Section: (D) Nitrosaminesmentioning
confidence: 99%
“…Additionally because some degradates are more stable than diuron, they can persist longer in the environment (table 1). Diuron can also be a disinfection by-product precursor; under certain water-treatment conditions, diuron can form N-nitrosodimethyl amine (NDMA) (Chen and Young, 2008), which is a class B2 carcinogen (reasonably considered to be a human carcinogen; U.S. Environmental Protection Agency 2010).…”
Section: Introductionmentioning
confidence: 99%